Building a rights-based approach to nutrition for women and children: harnessing the potential of women’s groups and rights-based organizations in South Asia - Monica Shrivastav; Vani Sethi; Avishek Hazra; Zivai Murira; Roopal Jyoti Singh; Krishna Wagh; Anuradha Nair; Veronica Kamanga Njikho; Sapna Desai (Frontiers in Public Health)
Women face numerous gender-based barriers that hinder their access to resources, nutritious foods, nutrition services, and maternity entitlements. Evidence shows that certain types of women’s groups can improve women’s access to resources and social capital and in some approaches also improve health and nutrition outcomes. Women’s rights-based organizations in South Asia have a longstanding tradition of collective action toward gender equality. Women’s rights-based organizations work in areas such as microfinance, livelihoods, women’s rights, health, and combating violence against women. In this perspective article, we explore how women’s groups and rights-based organizations can leverage their collective strength to advance nutrition outcomes for women and children. We identify seven pathways implemented through women’s groups toward improving nutrition outcomes. These pathways include (i) income generation, (ii) agriculture, (iii) health and nutrition behavior change communication and participatory learning and action, (iv) advocating for rights to better health and social services, (v) food access, (vi) cash transfers, and (vii) strengthening service delivery and fostering convergence with health systems. We also note that women’s groups have the potential to implement integrated interventions through combined food-systems-rights pathways. Investing in this area can support transforming nutrition policy from a service delivery model to a rights-based approach.